Applications of Differential Subordination for Argument Estimates of Multivalent Analytic Functions - Meng-Ting Lu; Ting Jia; Xing-Qian Ling; Jin-Lin Liu (Abstract and Applied Analysis)
By using the method of differential subordinations, we derive some properties of multivalent analytic functions. All results presented here are sharp.